Optimizing Property Tax Collection: E-KTP and Payment Reminder Approach: Mengoptimalkan Pemungutan Pajak Bumi dan Bangunan: Pendekatan E-KTP dan Pengingat Pembayaran - Mulyadi, Akhmad; Syahrorini , Syamsudduha; Ayuni , Shazana Dhiya; Rosidah , Izza; Negara, Fatahillah Okra (Indonesian Journal of Law and Economics Review, 2023)
This scientific article explores the importance of community involvement in regional development, emphasizing the collaborative efforts between government, citizens, and the business sector. The study focuses on the significant influence of local revenue on the progress of a region, where higher income correlates with improved development. However, certain areas face challenges due to the relatively low contribution of Property Tax (PBB) to Regional Original Income (PAD), mainly attributed to taxpayers' lack of awareness and occasional forgetfulness in meeting payment deadlines. In response, the research proposes an innovative approach to optimize PBB collection by leveraging e-KTP-based service queuing and payment reminders. The implementation of tax education programs covering various tax obligations, such as Pph, PPN, PBB, and Bea Materai, forms a critical aspect of this strategy. The results indicate promising advancements in revenue collection, underscoring the potential implications for sustainable regional development. Highlights: Efficient Collection: Implementing an E-KTP and payment reminder-based system improves the efficiency of property tax collection, ensuring timely payments and maximizing revenue for regional development. Citizen Awareness: Raising awareness among taxpayers about their obligations through tax education programs fosters a sense of civic responsibility and encourages voluntary compliance. Sustainable Development: Optimal property tax collection plays a pivotal role in financing sustainable regional development initiatives, contributing to improved infrastructure and public services. Keywords: Property Tax, PBB, E-KTP, Payment Reminder, Regional Development